Body Mass Index mediates the relationship between estimated glucose disposal rate and gallstones - Shuaipeng Yuan; Yuexia Lu; Zhun Xiao; Suping Ma (Scientific Reports)
Abstract This study examined the relationship between gallstones and estimated glucose disposal rate (eGDR) in people in the United States and the possible mediating function of body mass index (BMI). Data came from the National Health and Nutrition Examination Survey (NHANES), conducted between 2017 and March 2020. Logistic regression, subgroup analysis, smoothed curve fitting, and causal mediation studies were among the statistical techniques used to examine the participant data. There were 595 subjects with a gallstone diagnosis out of 5,656 total. A significant negative association between eGDR and gallstones was observed by fully adjusted multivariate logistic regression analysis with an OR of 0.90 and a 95% confidence interval (CI) of (0.83, 0.98). The mediation analysis indicated that BMI accounted for 58.58% of the relationship between eGDR and the occurrence of gallstones. This study identified a substantial non-linear negative relationship between the occurrence of gallstones and eGDR levels, with BMI acting as a mediating factor. A fresh viewpoint on gallstone therapy and prevention is offered by these findings.